High-Loading Self-Assembling Peptide Nanoparticles as a Lipid-Free Carrier for Hydrophobic General Anesthetics - Liu J (Dove Medical Press, 2021)
Jing Liu,1,2 Fei Peng,1,2 Yi Kang,1,2 Deying Gong,1,2 Jing Fan,1,2 Wensheng Zhang,1,2 Feng Qiu1,2 1Laboratory of Anesthesia and Critical Care Medicine, Department of Anesthesiology, Translational Neuroscience Center, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China; 2National-Local Joint Engineering Research Center of Translational Medicine of Anesthesiology, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of ChinaCorrespondence: Feng Qiu; Wensheng Zhang Email fengqiu@scu.edu.cn; zhang_ws@scu.edu.cnPurpose: Typical hydrophobic amino acids (HAAs) are important motifs for self-assembling peptides (SAPs), but they lead to low water-solubility or compact packing of peptides, limiting their capacity for encapsulating hydrophobic drugs. As an alternative, we designed a peptide GQY based on atypical HAAs, which could encapsulate hydrophobic drugs more efficiently. Although hydrophobic general anesthetics (GAs) have been formulated as lipid emulsions, their lipid-free formulations have been pursued because of some side effects inherent to lipids. Using GAs as targets, potential application of GQY as a carrier for hydrophobic drugs was evaluated.Methods: Thioflavin-T (ThT) binding test, dynamic light scattering (DLS) and transmission electron microscopy (TEM) were used to examine the self-assembling ability of GQY. Pyrene and 8-Anilino-1-naphthalenesulfonic acid (ANS) were used to confirm formation of hydrophobic domain in GQY nanoparticles. Using pyrene as a model, GQY’s capacity to encapsulate hydrophobic drugs was evaluated. GAs including propofol, etomidate and ET26 were encapsulated by GQY. Loss of righting reflex (LORR) test was conducted to assess the anesthetic efficacy of these lipid-free formulations. Paw-licking test was used to evaluate pain-on-injection of propofol-GQY (PROP-GQY) formulation. Hemolytic and cytotoxicity assay were used to evaluate biocompatibility of GQY.Results: Stable nanoparticles containing plenty of hydrophobic cavities could be formed by GQY, which could encapsulate hydrophobic drugs at very high concentration and form stable suspensions. Propofol, etomidate and ET26 formulated by GQY showed anesthetic efficacy comparable to their currently available formulations. Unlike clinic lipid emulsion, PROP-GQY formulation did not cause pain-on-injection in rats. Neither obvious cytotoxicity nor hemolytic activity of GQY was observed.Conclusion: GQY could encapsulate GAs to obtain stable and effective formulations. As a lipid-free carrier, GQY exhibited considerable biocompatibility and other side benefits such as reducing pain-on-injection. More SAPs based on atypical HAAs could be designed as promising carriers for hydrophobic drugs.Keywords: self-assembling peptides, nanoparticles, hydrophobic drugs, lipid-free formulations, general anesthetics